2021
DOI: 10.1111/infa.12389
|View full text |Cite
|
Sign up to set email alerts
|

The terrible twos: How children cope with frustration and tantrums and the effect of maternal and paternal behaviors

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 61 publications
3
7
0
2
Order By: Relevance
“…In both Clusters 1 and 2, children had higher scores of security than in Clusters 3 and 4, even if only the first cluster significantly differed from clusters 3 and 4. Consistently with the study by Deichmann and Ahnert (2021), children in a secure attachment relationship tended to experience frustration for a shorter time compared to children in an insecure attachment relationship. Indeed, the children with high levels of secure attachment would be significantly more likely to fall into the first cluster than in Clusters 3 and 4.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In both Clusters 1 and 2, children had higher scores of security than in Clusters 3 and 4, even if only the first cluster significantly differed from clusters 3 and 4. Consistently with the study by Deichmann and Ahnert (2021), children in a secure attachment relationship tended to experience frustration for a shorter time compared to children in an insecure attachment relationship. Indeed, the children with high levels of secure attachment would be significantly more likely to fall into the first cluster than in Clusters 3 and 4.…”
Section: Discussionsupporting
confidence: 83%
“…Cassidy, 1994). A recent study by Deichmann and Ahnert (2021) used the Experimental Frustration Procedures to examine toddlers' coping strategies and parents' supportive behaviours and found that children in a secure attachment relationship likely experienced frustration for a shorter period compared to children in an insecure attachment relationship.…”
Section: Sadness Regulation and Associated Variablesmentioning
confidence: 99%
“…Dessa forma, a criança apresenta-se resistente às interferências que atuam contra seus desejos. Essa oposição generalizada caracteriza uma transição da fase de dependência de bebê para a autonomia e iniciativa, comum as crianças desta idade (CÓRIA-SABINI, 1997;DEICHMANN;AHNERT, 2021).…”
Section: Introductionunclassified
“…Sendo assim, são apresentadas às normas e regras sociais basicamente através de reforço e punição de seus pais. Partindo deste processo de modelagem, a relação entre pais e filhos resulta em padrões de comportamento baseados em resposta e consequência (BERRYMAN;et al, 2002;DEICHMANN;AHNERT, 2021).…”
Section: Introductionunclassified
“…In contrast, joint play activities foremost challenge children's mental and language skills (e.g., Teufl et al., 2020), support child exploration (Grossmann et al., 2002), and regulate emotions when the child copes with frustration (e.g. Deichmann & Ahnert, 2021).…”
Section: Introductionmentioning
confidence: 99%